Letters of Lionginas Šepka (1907–1985) – a Glimpse into the Daily Routine of a Creator - Kiukienė, Dalia; Mieliauskienė, Marijona (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] This article deals with the analysis of the letters of legendary Lithuanian carver Lionginas Šepka (1907–1985), written in 1970–1977 from Lebedžiai village (Rokiškis district) and sent to Vilnius to his future wife, journalist Danutė Digrienė. With the help of these letters, we restore the details of the everyday life of L. Šepka, reveal the creator’s thoughts and feelings, household problems, social relationships and the need to create. During 7 years, L. Šepka wrote over 300 letters to D. Digrienė. Two decades after the death of L. Šepka, in 2006, she sent the following letters (309) to the Rokiškis Regional Museum. The first letter of L. Šepka was written in 1970; afterwards, every year, there were more and more of them: in 1971 – 34, in 1972 – 31, in 1973 – 42, in 1974 – 37, in 1975 – 39, in 1976 – 47 and in 1977 – 78 letters. The letters were written on the sheets of school notebooks, sometimes on pieces of the wallpaper. The letters were long, most of them consisted of 8–10 pages. They covered the entire life of Lionginas Šepka, all the events and thoughts, and in each letter, there was a expressed huge concern about Danutė. Those seven years of their correspondence give us a lot of information about the life of a common person in Lithuania of that time. This is a kind of a diary that is considered to be an important witness of a common person’s life in the 1980s.